Preparation and structures of nickel(II) compounds of 2, 9-meso-7, 14-rac-2, 5, 5, 7, 9, 12, 12, 14-octamethyl-1, 4, 8, 11-tetraazacyclotetradecane. (16th August 2017) - Curtis, Neil F.; Butcher, Raymond J.; Coles, Martyn P.; Wikaira, Jan
Graphical abstract: Preparations and structures are reported for compounds of 2 RS, 7 RS, 9 SR, 14 RS -[(2, 5, 5, 7, 9, 12, 14, 14-octamethyl-1, 4, 8, 11-tetrazacyclotetradecane)nickel(II)], [Ni( mr -L)] 2+ in: square-planar ([Ni( mr -L-V)](ClO4 )2 ), trans -octahedral ([Ni( mr -L-III)(NCS)2 ]), trigonal bipyramidal ([Ni( mr -L-V)Cl]ClO4 and [Ni( mr -L-V)](NCS)]ClO4 ) and cis -octahedral ([Ni( mr -V-L)(OAc)]ClO4 and [Ni( mr -V-L)(acac)]ClO4 ) coordination, where III and V indicate the nitrogen configurations 1 R, 4 S, 8 S, 11 R and 1 R, 4 S, 8 R, 11 S respectively. Abstract: Preparations and structures are reported for compounds of 2 RS, 7 RS, 9 SR, 14 RS -[(2, 5, 5, 7, 9, 12, 14, 14-octamethyl-1, 4, 8, 11-tetrazacyclotetradecane)nickel(II)] 2+ : trans -octahedral [Ni( mr -III-L)(NCS)2 ], cis -octahedral [Ni( mr -V-L)(OAc)]ClO4 (and –H2 O) with asymmetrical chelate acetato, [Ni( mr -V-L)(acac)]ClO4 and [Ni( mm1 -III L)]·2[Ni( mr -V-L)(acac)](ClO4 )4 with chelate pentane-2, 4-dionato, trigonal pyramidal [Ni( mr -V-L)Cl]ClO4 and [Ni( mr -V-L)(NCS)]ClO4 and square-planar [Ni( mr -V-L)](ClO4 )2, where III and V indicate the nitrogen configurations 1 R, 4 S, 8 S, 11 R and 1 R, 4 S, 8 R, 11 S respectively and mm1 -L is the 2 R, 7 S, 9 S, 14 R isomer of the amine. The preparations of [Ni( mr -V-L)(A)](ClO4 ), where A − = chelate nitrato, nitrito and μ-oxalato are reported.